The effect of fuel feed rate on temperature profiles of a cascading hearth with secondary swirl combustor - Wan Mohamed, Wan Ahmad Najmi; Ani, Farid Nasir (Faculty of Mechanical Engineering, 2002)
The abundant availability of biomass solid wastes in Malaysia such as palm shells from the oil palm industry promotes diversified research fields for its utilization. This paper investigates the application of a cascading hearth staged combustor to palm shells combustion in terms of fuel feed rate effect on temperature profiles. The application of a two-step hearth setup at primary stage combustion offers wider alternatives for solid phase combustion processes. Initial combustion studies of palm shells by controlled air combustion conditions using these set-ups show promising results for further development. Controlled air conditions promote gasification of the solid fuel and significantly lower combustor temperatures below 500oC. Varying the fuel feed at 0.1, 0.15 and 0.2 kg/min with constant air supply of 227 liters/min (8 CFM) and good fuel distribution on the hearth leads to fuel core temperatures exceeding 1000oC. As a result of high core temperatures, release rates of volatiles and combustible gases increases which influences attainable secondary combustion temperatures. The maximum secondary stage combustion exhaust temperature recorded was 490oC at 0.2 kg/min fuel feed, a secondary air supply of 42.5 liters/min (1.5 CFM) and a corresponding fuel core temperature of 1225oC.